Clusterin deficiency exacerbates cholestatic liver disease through ER stress and NLRP3 inflammasome activation - Hye-Young Seo; Ji Yeon Park; So-Hee Lee; Hye Won Lee; Eugene Han; Jae Seok Hwang; Mi Kyung Kim; Byoung Kuk Jang (Cell & Bioscience)
Abstract Background Cholestatic liver disease, characterized by impaired bile flow, leads to the accumulation of harmful metabolites and toxins, resulting in liver damage. Inflammatory cytokines are crucial for the progression of this condition. Clusterin is a glycoprotein with roles in cell death, lipid transport, and cellular protection. We previously demonstrated that clusterin protects against hepatic steatosis and hepatic fibrosis. This study explored the roles of clusterin in cholestatic liver injury induced by a DDC (3,5-diethoxycarbonyl-1,4-dihydrocollidine) diet. Methods The study evaluated the impact of clusterin on liver injury in C57BL/6 mice and clusterin-knockout (KO) mice fed a DDC diet for 10–20 days. Primary Kupffer cells (KCs) and hepatocytes (HCs) of these mice were analyzed. Techniques such as Sirius red staining, immunohistochemistry, real-time RT-PCR, enzyme-linked immunosorbent assays, and western blotting were performed to assess the effects of clusterin. Results Clusterin expression was upregulated in the cholestatic liver. Clusterin-KO mice exhibited elevated levels of alanine aminotransferase, aspartate aminotransferase, collagen, and αSMA upon DDC diet-induced liver injury. They also had increased levels of markers of endoplasmic reticulum (ER) stress (CHOP, ATF6, and p-eIF2α) and inflammasome activity (NLRP3, ASC, caspase-1, and interleukin 1 beta (IL1β) protein expression, and IL1β and interleukin 18 secretion). Thapsigargin, an ER stress inducer, heightened NLRP3 inflammasome activation in primary KCs and HCs, which was mitigated by overexpression of clusterin. Conclusions The absence of clusterin exacerbates ER stress and NLRP3 inflammasome activation in mice fed a DDC diet. Conversely, overexpression of clusterin suppresses these stress responses. Thus, clusterin deficiency is associated with an enhanced inflammasome response in the liver that is linked to upregulation of ER stress.